2022
DOI: 10.1002/brb3.2527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal ions on Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a degenerative disease of the nervous system. The typical pathological changes of AD are Aβ deposition, neurofibrillary tangles, neuron loss, and chronic inflammation. The balance of metal ions is essential for numerous physiological functions, especially in the central nervous system. More studies showed that metal ions participate in the development of AD. However, the involvement of metal ions in AD is controversial. Thus, we reviewed articles about the relationship between metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…In swift, dysfunction in cellular organelles like mitochondria 27 , endoplasmic reticulum due to unfolded protein response (UPR) 28 , augmentation of metal ions in neuritic plaques 29 and hyperactivation of microglia followed by the upregulation of NADPH oxidase 30 are characterized by ROS/RNS production 31 in AD. Oxidative stress can accelerate the aggregation of Aβ and vice versa.…”
Section: Oxidative Stress In Admentioning
confidence: 99%
“…In swift, dysfunction in cellular organelles like mitochondria 27 , endoplasmic reticulum due to unfolded protein response (UPR) 28 , augmentation of metal ions in neuritic plaques 29 and hyperactivation of microglia followed by the upregulation of NADPH oxidase 30 are characterized by ROS/RNS production 31 in AD. Oxidative stress can accelerate the aggregation of Aβ and vice versa.…”
Section: Oxidative Stress In Admentioning
confidence: 99%
“…It has been suggested that copper dysmetabolism may play a role for the progression of AD [ 77 , 78 ] since the extra-neuronal plaques containing amyloid-beta peptide (Aβ) have been found to be enriched with Cu. However, the role of copper and iron in the progression of AD is still a matter of debate [ 16 , 17 ]. It has been claimed that anti-copper therapy may affect positively a certain percentage of AD patients [ 79 ] in agreement with the alleged existence of different subtypes of AD [ 80 ].…”
Section: Chelator Combination Versus Monotherapy As Therapeutic Strategymentioning
confidence: 99%
“…Although exogenous Cu intoxications are rare, dysregulations in the Cu metabolism may lead to Cu retention and neurological disorders, as seen in Wilson’s disease [ 15 ]. Furthermore, Cu dysmetabolism seems to play a role in the pathophysiology of Alzheimer’s disease (AD) [ 5 ], although it should be emphasized that the role of metal ions in the AD pathogenesis is still a matter of controversy [ 16 , 17 ]. Thus, it has been suggested that some metal transthyretin complexes provide a protective response against the AD development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] For instance, Cu 2+ levels in the blood of Alzheimer's disease (AD) patients are usually high, and this change is related to the involvement of Cu 2+ in regulating various AD pathogenesis mechanisms such as oxidative stress, inflammatory damage, and Aβ metabolism disorders, suggesting that the occurrence and development of AD can be predicted by detecting changes in Cu 2+ levels in the blood. 9,10 Moreover compared with the collection of the cerebrospinal fluid for detection of Aβ and Tau, blood is easier to obtain and repeatedly sampled, more simple to manipulate, and thus may have a wider range of applications. In conclusion, the quantitative and morphological analysis of metal ions in the human body is crucial to investigate complicated biological processes and prevent, detect, and treat diseases.…”
Section: Introductionmentioning
confidence: 99%